2013
DOI: 10.1063/1.4827425
|View full text |Cite
|
Sign up to set email alerts
|

Theory and experiment on resonant frequencies of liquid-air interfaces trapped in microfluidic devices

Abstract: Bubble-based microfluidic devices have been proven to be useful for many biological and chemical studies. These bubble-based microdevices are particularly useful when operated at the trapped bubbles' resonance frequencies. In this work, we present an analytical expression that can be used to predict the resonant frequency of a bubble trapped over an arbitrary shape. Also, the effect of viscosity on the dispersion characteristics of trapped bubbles is determined. A good agreement between experimental data and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
0
23
3
Order By: Relevance
“…Therefore the velocity of the acousticinduced flow was maximal when the driving frequency was 5-6 kHz. This frequency was smaller than the theoretical resonance frequency (7.9 kHz) of the 400 µm wide rectangular bubble calculated using the equation in literature (Chindam et al 2013). This might be related to the shape of the air/liquid interface.…”
Section: Parametric Study Of Mixingcontrasting
confidence: 59%
See 1 more Smart Citation
“…Therefore the velocity of the acousticinduced flow was maximal when the driving frequency was 5-6 kHz. This frequency was smaller than the theoretical resonance frequency (7.9 kHz) of the 400 µm wide rectangular bubble calculated using the equation in literature (Chindam et al 2013). This might be related to the shape of the air/liquid interface.…”
Section: Parametric Study Of Mixingcontrasting
confidence: 59%
“…The resonance frequencies of rectangular air bubbles in water are given by the equation reported by Chindam et al (Chindam et al 2013), and are found to be 12.6, 8.9 and 7.9 kHz for bubbles with the width of 100, 200 and 400 µm, respectively.…”
Section: Microfluidic Chip Designmentioning
confidence: 96%
“…Similarly, capillary waves are used to study wave turbulence experimentally [18][19][20] as well as numerically [21,22]. In cell biology, capillary waves influence the behavior and properties of lipid membranes, micelles and vesicles [23][24][25], and with respect to microfluidic applications, capillary waves are of central interest to applications such as surface wave acoustics [26], microstreaming [27] and ultrasound cavitation [28].…”
Section: Introductionmentioning
confidence: 99%
“…This frequency is mainly a function of geometrical bubble parameters and can be theoretically estimated. 29 However, the resonant frequency can also be experimentally determined by visual observation due to the limited predictability of the models 16 and fabrication tolerances of the 3D printed moulds. Briefly, a frequency sweep is performed using a signal generator, and the microstreaming phenomenon is observed under the digital microscope.…”
Section: Resonant Frequencymentioning
confidence: 99%